PERBEDAAN PRESTASI BELAJAR IPS TERPADU SISWA YANG DIAJAR DENGAN MENGGUNAKAN METODE TWO STAY TWO STRAY (TSTS) DIBANDINGKAN DENGAN MENGGUNAKAN METODE CERAMAH - Anna resha; Sumadi Sumadi; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2013)
The objective of this research is to find out the difference of learning achievement students who are taught by using Two Stay Two Stray (TSTS) method and they who are taught by using Communicative Learning in integrated social science at the second grade of junior high school Negeri 2 Ambarawa Pringsewu. This research used quasi experimental method. The researcher has determined the sample by using purposive sampling. The sample which determined consists of two classes they are student class VIII.1 as the experimental class and student class VIII.2 as the control class. Quantitative data was gained directly from the subject of the research by giving the pre-test and post-test in learning of Geographic condition and inhabitant material. In analyzing the data used hypothesis testing used normality testing, homogeneity testing, similarity testing of two averages and difference testing of two averages. Based on the results of this study concluded that there are significant differences between the activity and the learning achievement of students who use the lecture method of teaching with students using the Two Stay Two Stray (TSTS) after being treated. This is evidenced by the acquisition of the average classroom student achievement experiments (VIII.1 at 76.06 while the control class (VIII.2) of 71.93. Feat t test of the two parties do, obtained at 1.711 greater thitung from 1.67 ttable so Ho is rejected, so that there is a difference between the learning outcomes of students taught by cooperative learning techniques Two Stay Two Stray (TSTS) learning lectures. Keywords: cooperative learning, Two Stay Two Stray